PEMBUATAN TEH DARI DAUN GAHARU JENIS Gyrinops versteegii - Samsuri, Taufik; Fitriani, Herdiyana (Bioscientist : Jurnal Ilmiah Biologi, 2013)
Gaharu is a product of Non Timber Forest which is very potential and high economic value in West Nusa Tenggara Province. Lombok Island is one of the gaharu producing areas in Indonesia and is a growing place of endemic gaharu commercial species such as Gyrinops versteegii. Local people call it "Cucumber". So far, gaharu farmers only use gaharu trees only to be sold to gaharu exporters. However, in fact gaharu leaves can be processed into a product that has a good economic value, which is made into tea. Gaharu leaf tea is believed to have efficacy for the drinker. Gaharu leaf tea is usually made from leaves or young shoots of gaharu trees that have not been inoculated. While the gaharu leaves tea production from inoculated trees has not been done. Thus the purpose of this research is to optimize the utilization of agarwood leaf that has been inoculated as a tea-making material, so it can produce gaharu leaf tea with good quality without loss of taste, aroma, and its benefits. Types This research is experimental through laboratory test including water content test and extract level with gravimetric method. The material used as the assessment is Gaharu alpha leaves of Gyrinops versteegii taken directly from the gaharu farmer’s garden on Lombok island.